Healthy lifestyle before and during pregnancy to prevent childhood obesity: study protocol for a parallel group randomised trial — the PRE-STORK trial - Tina Vilsbøll; Signe S Torekov; Julie Lyng Forman; Romain Barrès; Andreas Andersen; Filip K Knop; Signe Foghsgaard; Klaus Bønnelykke; Thomas Bergholt; Karoline Kragelund Nielsen; Christina Anne Vinter; Majken Lillholm Pico; et al. (BMJ Open)
Introduction The global prevalence of people living with overweight has tripled since 1975 and more than 40% of Danish women enter pregnancy being overweight. With the increasing rates of obesity observed in children, adolescents and adults, there is an urgent need for preventive measures. Risk factors for childhood obesity include maternal overweight or obesity before conception and excessive weight gain during pregnancy. Interventions aimed at modifying maternal lifestyle during pregnancy have demonstrated minimal positive or no impact on the health of the children. The ‘healthy lifestyle before and during pregnancy to prevent childhood obesity — the PRE-STORK trial’ aims to provide insights into the effect of a lifestyle intervention initiated before conception and continued during pregnancy in women with overweight or obesity, on neonatal adiposity in their children.Methods and analysis In this randomised, two-arm, parallel-group, controlled trial, we will include 360 women with overweight or obesity (aged 18–40; body mass index 25–44 kg/m2) and their partners. The women will be randomised to receive either standard of care or a lifestyle intervention focused on preconception body weight reduction, regular physical exercise, healthy diet and support from a mentor before and during pregnancy. The primary outcome is the difference in neonatal adiposity measured in their children at birth. Children conceived during the trial will constitute a birth cohort, monitoring the effects on their health until the age of 18 years.Ethics and dissemination The trial has been approved by the Regional Committee on Health Research Ethics in the Capital Region of Denmark (identification number H-22011403) and will be conducted in agreement with the Declaration of Helsinki. All results, whether positive, negative and inconclusive, will be disseminated at national or international scientific meetings and in peer-reviewed scientific journals.Trial registration number ClinicalTrials.gov: NCT05578690 (October 2022).